Possibilities and limits of adhesive layer thickness optical evaluation - Müller, Miroslav; Náprstková, Nataša (Manufacturing Technology Journal, 2010)
The uniform adhesive layer thickness belongs to the key criterions of the bonded joint formation. On the basis of long-term laboratory findings it was evaluated as one of basic effects on the strength changes. This fact leads to the objective evaluation necessity and to the technical practice respecting. The carried out laboratory experiments are indicative of the incongruity between the expected adhesive layer thickness and the real value determined in the bonded joint square cut using the microscope.
Keywords: Adhesive bond; adhesive layer thickness; microscope